2022
DOI: 10.1007/s00109-022-02254-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron and iron-related proteins in alcohol consumers: cellular and clinical aspects

Abstract: Alcohol-associated liver disease (ALD) is one of the most common chronic liver diseases. Its pathological spectrum includes the overlapping stages of hepatic steatosis/steatohepatitis that can progress to liver fibrosis and cirrhosis; both are risk factors for hepatocellular carcinoma. Moreover, ALD diagnosis and management pose several challenges. The early pathological stages are reversible by alcohol abstinence, but these early stages are often asymptomatic, and currently, there is no specific laboratory bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…But interestingly, non-drinkers and even nonsmokers in this study had higher sTfR levels instead. One previous study summarized that alcohol could alter the levels of some iron-related proteins, including serum iron, hepcidin and transferrin, which was not the case for sTfR (27). It indicated that there might be a more complex indirect interaction between alcohol consumption, sTfR and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…But interestingly, non-drinkers and even nonsmokers in this study had higher sTfR levels instead. One previous study summarized that alcohol could alter the levels of some iron-related proteins, including serum iron, hepcidin and transferrin, which was not the case for sTfR (27). It indicated that there might be a more complex indirect interaction between alcohol consumption, sTfR and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements play an important role in human health and disease. For example, the role of iron in various diseases, including liver fibrosis, alcohol-related liver disease, and COVID-19, has been reviewed [157][158][159][160].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have revealed that there are change in iron metabolism in substance use disorders including alcohol abuser. 28 31 , 52 , 53 A study conducted in chronic cocaine user revealed that iron content was significantly higher in basal ganglia reward regions than that of control individuals. 54 It was also reported that iron mediates morphine -induced ferritin heavy chain upregulation.…”
Section: Discussionmentioning
confidence: 99%